2020
DOI: 10.3390/nu12113352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on Lipid Profile in Adults with the Metabolic Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Metabolic syndrome (MetS) increases the risk of cardiovascular disease, with atherogenic dyslipidemia being a major contributing factor. Methods: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement to assess whether vitamin D supplementation (VDS) alleviates dyslipidemia in adults with MetS. Scientific databases (PUBMED, MEDLINE, CINAHL, EMBASE, Cochrane Library, ClinicalTrials.gov, International Clinical Trials Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 53 publications
4
39
0
3
Order By: Relevance
“…Triglycerides and HDL-cholesterol generally have an inverse association ( 102 , 103 ), which we confirmed in this study (Spearman's coefficient of correlation = −0.615, p < 0.001), and the linear regression analysis identified only triglycerides as significant predictors of VitD levels. Interestingly, and in line with this study findings, some studies show that VitD supplementation increased the levels of triglycerides ( 104 106 ), even though both unchanged ( 107 – 109 ) and decreased ( 110 ) levels were found in other studies. Therefore, we hypothesize that the observed positive relationship of VitD with serum triglycerides reflects the effect of positive association with lipolysis after an enduring physical work ( 89 ).…”
Section: Discussionsupporting
confidence: 91%
“…Triglycerides and HDL-cholesterol generally have an inverse association ( 102 , 103 ), which we confirmed in this study (Spearman's coefficient of correlation = −0.615, p < 0.001), and the linear regression analysis identified only triglycerides as significant predictors of VitD levels. Interestingly, and in line with this study findings, some studies show that VitD supplementation increased the levels of triglycerides ( 104 106 ), even though both unchanged ( 107 – 109 ) and decreased ( 110 ) levels were found in other studies. Therefore, we hypothesize that the observed positive relationship of VitD with serum triglycerides reflects the effect of positive association with lipolysis after an enduring physical work ( 89 ).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, Farrokhian et al found no significant changes in lipid profile after vitamin D supplementation, although they reported changes in plasma malonaldehyde levels, which results from lipid peroxidation [147]. Similarly, AlAnouti et al reports inconsistent results on the relationship between vitamin D status and dyslipidemia in MS adults, pointing mainly to a lack of effect, despite improved vitamin D status [148]. However, the authors indicate that these results should be interpreted with caution given the limited number of included clinical trials RCTs, the small sample size, and the limited intervention period.…”
Section: Vitamin D and Metabolic Syndrome: Intervention Studiesmentioning
confidence: 99%
“…One-year supplementation with vitamin D 3 at 4000 IU/day did not affect CVD, lipid profiles, or C-reactive protein levels in patients with type 2 diabetes, but did lower triglyceride (TG) levels [150]. Another trial reported that supplementation with vitamin D at 150,000 IU every 3 months failed to alter inflammatory markers and lipids in adults with metabolic syndrome [151]. A Cochrane review including 159 RCTs suggested that vitamin D supplementation may reduce all-cause mortality compared with placebo or no intervention, but had no significant effect on cardiovascular mortality [152] (Table 3).…”
Section: Cardiovascular Diseasementioning
confidence: 99%